Irradiation of a whitefly by submocrosecond electron beam at atmospheric pressure; Gas Discharge Plasmas and Their Applications (GDP 2019) - Isemberlinova A. A. Asemgul Asentaevna; Nuzhnyh S. A.; Poloskov A. V. Artem Viktorovich; Serebrennikov M. A. Maksim Anatolevich; Egorov I. S. Ivan Sergeevich (2019, 2019)
Заглавие с титульного экрана